2016
DOI: 10.1007/s10815-016-0696-2
|View full text |Cite
|
Sign up to set email alerts
|

The pellet swim-up is the best technique for sperm preparation during in vitro fertilization procedures

Abstract: Purpose The aim of this study was to investigate the most suitable sperm preparation technique to apply in order to obtain a spermatozoon population with minimal DNA damage during in vitro fertilization procedures. We compared four preparation techniques: direct swim-up (DSU), pellet swimup (PSU), density gradient (DG), and density gradient followed by swim-up (DG-SU), evaluating the effects of each technique on the DNA damage rate, evaluated by DNA fragmentation index of the spermatozoa obtained. Methods In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
58
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 24 publications
2
58
1
2
Order By: Relevance
“…Amiri and colleagues found that the number of DNA-fragmented spermatozoa in samples prepared by the SU method was larger than those in samples processed with the DGC approach32. However, some studies have found that the mean DNA fragmentation in samples processed by DGC was higher than in samples collected with the SU method3334. Telomeres are fundamental for genome integrity17.…”
mentioning
confidence: 99%
“…Amiri and colleagues found that the number of DNA-fragmented spermatozoa in samples prepared by the SU method was larger than those in samples processed with the DGC approach32. However, some studies have found that the mean DNA fragmentation in samples processed by DGC was higher than in samples collected with the SU method3334. Telomeres are fundamental for genome integrity17.…”
mentioning
confidence: 99%
“…The commonly used methods for sperm preparation in routine ART are the swim‐up method and density gradient centrifugation. These methods aid in the selection of an available spermatozoon with a normal morphology and help decrease the ratio of spermatozoa with DNA fragmentation (Volpes et al., ). Additionally, spermatozoa with DNA fragmentation could be reduced by recurrent ejaculation (every 24 hr for 4 days) combined with using density gradient centrifugation, which would lead to a significant increase in pregnancy rates with ICSI using such spermatozoa (Sánchez‐Martín et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies reported that a combination technique of density-gradient centrifugation and swim-up (DGC-SU) was more effective in enriching sperm cells with normal morphology and eliminating sperm cells with DNA fragmentation than DGC technique alone [4][5][6][7]. Given this, the DGC-SU technique is more widely used in the field of ART work concerning sperm preparation compared to DGC technique alone at the present time in China.…”
Section: Introductionmentioning
confidence: 99%
“…This finding suggests that density-gradient centrifugation should be avoided during sperm preparation [19]. In addition, the DGC-SU technique requires operators to transfer sperm sample among several tubes, thereby increasing the potential risk of mismatches [5,[20][21]. These limitations, in concert, suggested that the DGC-SU was not optimal technique for sperm preparation for IVF and ICSI treatments.…”
Section: Introductionmentioning
confidence: 99%